2007
DOI: 10.1371/journal.ppat.0030033
|View full text |Cite
|
Sign up to set email alerts
|

Outer Surface Protein B Is Critical for Borrelia burgdorferi Adherence and Survival within Ixodes Ticks

Abstract: Survival of Borrelia burgdorferi in ticks and mammals is facilitated, at least in part, by the selective expression of lipoproteins. Outer surface protein (Osp) A participates in spirochete adherence to the tick gut. As ospB is expressed on a bicistronic operon with ospA, we have now investigated the role of OspB by generating an OspB-deficient B. burgdorferi and examining its phenotype throughout the spirochete life cycle. Similar to wild-type isolates, the OspB-deficient B. burgdorferi were able to readily i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
89
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 50 publications
2
89
1
Order By: Relevance
“…Several plasmids, such as lp25, lp28-1 and lp36, are essential for borrelial infectivity (Jewett et al, 2007;Purser & Norris, 2000;Stewart et al, 2005). Plasmid lp54 has been implicated as being important for the survival of B. burgdorferi in both tick and mammalian hosts, largely because of the presence of the ospAB and dbpBA operons (Caimano et al, 2005;Hagman et al, 1998;Neelakanta et al, 2007;Shi et al, 2008;Yang et al, 2004). Many other genes encoded on lp54 have been found to be differentially regulated in response to temperature, pH and other mammalian-derived signals, which are presumed to be mediated, at least in part, by RpoS (Caimano et al, 2005;Clifton et al, 2006;Ojaimi et al, 2003;Revel et al, 2002).…”
Section: Genes Regulated By Rrp2 Rpon and Rposmentioning
confidence: 99%
See 2 more Smart Citations
“…Several plasmids, such as lp25, lp28-1 and lp36, are essential for borrelial infectivity (Jewett et al, 2007;Purser & Norris, 2000;Stewart et al, 2005). Plasmid lp54 has been implicated as being important for the survival of B. burgdorferi in both tick and mammalian hosts, largely because of the presence of the ospAB and dbpBA operons (Caimano et al, 2005;Hagman et al, 1998;Neelakanta et al, 2007;Shi et al, 2008;Yang et al, 2004). Many other genes encoded on lp54 have been found to be differentially regulated in response to temperature, pH and other mammalian-derived signals, which are presumed to be mediated, at least in part, by RpoS (Caimano et al, 2005;Clifton et al, 2006;Ojaimi et al, 2003;Revel et al, 2002).…”
Section: Genes Regulated By Rrp2 Rpon and Rposmentioning
confidence: 99%
“…bba16 (ospB), which belongs to the ospAB operon that is essential for B. burgdorferi colonization and survival within tick midguts (Neelakanta et al, 2007;Yang et al, 2004), was downregulated 3.6-, 2.1 and 1.8-fold, respectively, by Rrp2, RpoN and RpoS. In our test, we also found that bba15 (ospA) was downregulated 1.8-, 1.3-and 1.3-fold, respectively, by Rrp2, RpoN and RpoS.…”
Section: Genes Likely Regulated By Rrp2 Rpon and Rposmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, extensive efforts have been directed toward elucidating the mechanisms by which Bb cycles, adapts, and sustains itself in these diverse niches. It is now well established that outer surface (lipo)protein C (OspC), OspA/B, decorin-binding protein B/A (DbpB/A), PncA, and BptA are required by Bb for efficient infection of ticks or mammalian hosts (4)(5)(6)(7)(8)(9)(10). It is also generally accepted that the recently discovered Rrp2-RpoN ( 54 )-RpoS ( S ) regulatory pathway plays prominently in Bb's virulence expression (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Subsequent studies suggest that OspA is an adhesin, important for retaining spirochetes in the tick midgut until feeding [161][162][163]. OspB, another potential midgut adhesin [164], BptA, a lipoprotein of unknown function, and the product of the BB0690 gene, which is probably involved in resistance to oxidative stress [165], also appear to contribute to bacterial survival in ticks [166][167][168]. The RpoN-RpoS regulatory cascade appears to be required for migration of spirochetes to the salivary glands during transmission, but not for survival within the tick environment [153].…”
Section: B Burgdorferi Infection Of Ticksmentioning
confidence: 99%